Emergency management of older people with cervical spine injuries: an expert practice review. Issue 4 (3rd August 2021) - Benchetrit, Sandy; Blackham, Jules; Braude, Philip; Halliday, Ruth; Shipway, David; Williams, Adam; Carlton, Edward
Abstract : Spinal fractures are the third most common traumatic injury in older people, of which cervical spine injuries make up around 15%. They are predominantly seen in people living with frailty who fall from standing height. Spinal fractures in this patient group are associated with substantial morbidity and mortality (over 40% at 1 year). For many older people who survive, their injuries will be life changing. Practice between EDs varies significantly, with no universally accepted guidelines on either assessment, investigation or management specific to older people experiencing trauma. This expert practice review examines the current evidence and emergency management options in this patient group through clinical scenarios, with the aim of providing a more unified approach to management.